The Therapeutic Effect of Curcumin in Quinolinic Acid-Induced Neurotoxicity in Rats is Associated with BDNF, ERK1/2, Nrf2, and Antioxidant Enzymes - Ricardo A. Santana-Martínez; Carlos A. Silva-Islas; Yessica Y. Fernández-Orihuela; Diana Barrera-Oviedo; José Pedraza-Chaverri; Rogelio Hernández-Pando; Perla D. Maldonado (MDPI AG, 2019)
In the present study we investigated the participation of brain-derived neurotropic factor (BDNF) on the activation of the mitogen activated protein kinase (MAPK) protein extracellular signal-regulated kinase-1/2 (ERK1/2) as a mechanism of curcumin (CUR) to provide an antioxidant defense system mediated by the nuclear factor erythroid 2-related factor 2 (Nrf2) in the neurotoxic model induced by quinolinic acid (QUIN). Wistar rats received CUR (400 mg/kg, intragastrically) for 6 days after intrastriatal injection with QUIN (240 nmol). CUR improved the motor deficit and morphological alterations induced by QUIN and restored BDNF, ERK1/2, and Nrf2 levels. CUR treatment avoided the decrease in the protein levels of glutathione peroxidase (GPx), glutathione reductase (GR), γ-glutamylcysteine ligase (γ-GCL), and glutathione (GSH) levels. Only, the QUIN-induced decrease in the GR activity was prevented by CUR treatment. Finally, QUIN increased superoxide dismutase 2 (SOD2) and catalase (CAT) levels, and the γGCL and CAT activities; however, this increase was major in the QUIN+CUR group for γ-GCL, CAT, and SOD activities. These data suggest that the therapeutic effect of CUR could involve BDNF action on the activation of ERK1/2 to induce increased levels of protein and enzyme activity of antioxidant proteins regulated by Nrf2 and GSH levels.